Microstrip Triband Bandstop Fitler with Sharp Stop Band Skirts and Independently Controllable Second Stop Band Response - Kishor Kumar Adhikari; Nam-Young Kim (The Scientific World Journal)
This paper presents a compact planar triband bandstop filter (TBBSF) with compact size and high selectivity. The structure of the filter incorporates two folded trisection stepped-impedance resonators (TSSIRs). One of these resonators is designed to operate at the first and third center frequencies and the other resonator is designed to operate at the second center frequency of the proposed filter. To achieve a compact size filter, alternating impedance lines of the resonators are folded widthwise and also one resonator is embedded within another. Theoretical analysis and design procedures are described, including the synthesis equations for each resonator. The main advantage of the proposed method is that the filter provides flexibility to tune the second center frequency and control the corresponding bandwidth without changing the first and third stop band response. Additionally, several reflection zeros (RZs) are introduced in the pass band to improve its flatness. To demonstrate the feasibility of the proposed design method, both the first and second order TBBSFs were designed, simulated, and fabricated, with center frequencies of 1.92 GHz, 3.55 GHz, and 5.5 GHz.